Allegorical figures at Flora Fountain - Ghosh, Ayan (Jio Institute, 2023)
Flora Fountain was built in honor of Sir Bartle Frere, who laid out plans to restructure Bombay along the newly laid out east-west axis (from Town Hall to Churchgate Station) and the north-south axis (from CSMT to Gateway of India).